Implications of Executorial Strength of Fiducia Security Certificate after Decision Constitutional Court No. 18/PUU-XVII/2019 Concerning Notary Assets - Sutrisno Purwohadi; Theresa Irene Sumartoni (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
Fiduciary material rights are guaranteed. The collateral objects are tangible, intangible and immovable objects that cannot be guaranteed with mortgages. Fiduciary collateral is widely used by finance companies. Debtor defaults, the leasing party executes fiduciary objects unilaterally, this is considered contrary to the 1945 Constitution. Article 15 paragraph (2) and Article 15 paragraph (3) of Act No 42 of 1999 concerning Fiduciary Guarantee is subjected to a material test. After Constitutional Court Number 18/PUU-XVII/2019, Execution of fiduciary guarantees after the decision of the, after Constitusional Court, creditors cannot execution guarantee directly because executorial beslag in fiduciary certificate which have power same with court decision has been canceled. According to Constitutional Court’s decision Number 18/PUU-XVII/2019 states that Article 15 paragraph (2) and Article 15 paragraph (3) of Act No 42 Year 1999 is contradictory to the 1945 Constitution. After the Constitutional Court's Decision No. 18/PUU-XVII/2019 states that the execution of guarantees cannot be carried out unilaterally by creditors, but must be through a District Court decision, unless there is an agreement on breach of contract between the debtor and the creditor and the debtor voluntarily submits the object of fiduciary collateral, this matter impact to lack of creditor’s interest to give loan with moveable object remember executory process need long time and many cost because execution object fiduciary guarantee must be district court decision. Notary as formulate’s agreement must be think carefully to response Constitutional Court Number 18/PUU-XVII/2019 with strengthen clause in fiduciary guarantee deed based on credit agreement which has been made the parties so that occur balanced right and obligation between creditor and debtor. Therefore author take theme about Notary’s role to make Notary’s deeds especially fiduciary guarantee’s deed after Constitutional Court Number 18/PUU-XVII/2019 with research’s method use literature research in the form of juridical data. The research is normative juridical and qualitative research type Research methods.